Convolution for The Offset Linear Canonical Transform with Gaussian Weight and Its Application - Thai Ha, Quan; Tien Minh, Lai; Minh Tuan, Nguyen (VNU Journal of Science: Mathematics - Physics, 2019)
Abstract: This paper presents the convolution for the offset linear canonical transform (OLCT) with the Gaussian weight and its applications. The product theorem is also studied. In applications, some ways to design the filters in the OLCT domain as well as the multiplicative filter and the Gaussian filter are introduced. Keywords : Reconstruction, Shannon theorem, convolution, filter, signal, offset linear canonical transform, fractional Fourier transform, Fourier transform.